Creative strategies : idea management for marketing, advertising, media and design - Pricken, Mario (Thames & Hudson, 2010)
Suitable for all designers and advertising creatives, this book showcases 230 amazing ad campaigns from all over the world. Mario Pricken identifies the keys to their success and demonstrates how brilliant ideas can be used to forge more fruitful relationships between creatives and clients